Mental health of individuals at increased suicide risk after hospital discharge and initial findings on the usefulness of a suicide prevention project in Central Switzerland - Werdin, Sophia; Fink, Günther; Rajkumar, Sarah; Durrer, Michael; Gurtner, Caroline; Harbauer, Gregor; Warnke, Ingeborg; Wyss, Kaspar (Frontiers in Psychiatry, 2024)
Background: Supporting individuals in managing their suicidality can prevent suicidal behavior. This study evaluated the suicide prevention project SERO, which was launched in Central Switzerland in 2021. SERO comprises four components: the suicide risk assessment technique PRISM-S, a personal safety plan, mental health first aid courses for relatives, and a self-management app. We assessed the mental health of individuals at increased suicide risk after hospital discharge and evaluated the usage and usefulness of SERO components. Methods: A cross-sectional study targeted former patients of Lucerne Psychiatry with an increased suicide risk. Between March 2023 and March 2024, we collected data from 24 individuals through a questionnaire administered six months post-discharge. Descriptive statistics characterized sociodemographics, assessed self-efficacy, self-management, and health literacy, and analyzed the usage and usefulness of SERO components. Associations between the usage of SERO components and mental health outcomes were investigated using Wilcoxon rank sum tests. Results: Mental health assessments indicated, on average, low to moderate levels of self-efficacy, self-management, and health literacy, with substantial variations across individuals. Participants’ exposure to SERO components varied: 83% used PRISM-S for suicide risk assessment, 67% developed a personal safety plan, 38% used the SERO app, and 8% reported that their relatives participated in a mental health first aid course. 50% of safety plan users and 44% of SERO app users found the tools helpful before or during a suicidal crisis. 78% of SERO app users would recommend the app to others. Conclusion: Low to moderate levels of self-efficacy, self-management, and health literacy underscore the need for targeted interventions to support individuals at suicide risk. Positive feedback on the personal safety plan and the SERO app suggests their potential effectiveness in helping individuals manage their suicidality. Therefore, integrating structured measures for promoting self-management into standard care protocols in psychiatric hospitals and into patients’ lives may contribute to preventing suicides. The main limitation of our study is its small sample size. Future larger-scale studies should investigate user experiences in detail, assess the causal effects of SERO components on specific mental health and suicide outcomes, and evaluate the cost-effectiveness of each component separately and in combination.